Imprints of Eddy Stirring and Trapping Effects on Global Salt Transport - Yikai Yang; Lili Zeng; Qiang Wang; Rui Shi; Peng Xiu (Earth's Future)
Abstract Oceanic eddy‐induced salt transport is highly important for the global water cycle and climate change. Previous studies have focused on single horizontal eddy‐induced transport effect or regional studies, yet assessments of the impact of stirring and trapping effects on salt transport at the global scale are incomplete. Here, we show that upper ocean salt transport due to eddy stirring and trapping effects displays a strong zonal dependence on the global ocean, with the former playing a dominant role over the analysis period. The zonal accumulation of meridional salt transport reaches a maximum of −4.52 psu·Sv (×106 psu·m3·s−1) in the Southern Ocean. Equivalent freshwater transport is poleward in the near‐equator region and equatorward in the near‐polar region, consequently causing freshwater to converge in the middle of the subtropical gyre. The divergence of salt transport further suggests that eddies transport salt out of the maximum sea surface salinity regions. Strong seasonal variations in salt transport occur mainly in eddy‐enriched regions such as the western boundary currents and the Southern Ocean. The relative contribution of eddy stirring and trapping effects to oceanic meridional salt transport can reach approximately 23.6%. These results highlight the importance of eddy effects in the global oceanic salt budget.